Inhibitory effects of lysozyme on endothelial protein C receptor shedding in vitro and in vivo - Ku, Sae-Kwang; Yoon, Eun-Kyung; Lee, Hyun Gyu; Han, Min-Su; Lee, Taeho; Bae, Jong-Sup (BMB reports, 2015)
Lysozyme protects us from the ever-present danger of bacterial infection and binds to bacterial lipopolysaccharide (LPS) with high affinity. Beyond its role in the activation of protein C, the endothelial cell protein C receptor (EPCR) plays an important role in the cytoprotective pathway. EPCR can be shed from the cell surface, which is mediated by tumor necrosis factor-α converting enzyme (TACE). However, little is known about the effects of lysozyme on EPCR shedding. We investigated this issue by monitoring the effects of lysozyme on phorbol-12-myristate 13-acetate (PMA)-, tumor necrosis factor (TNF)-α-, interleukin (IL)-1β-, and cecal ligation and puncture (CLP)-mediated EPCR shedding and underlying mechanism. Data demonstrate that lysozyme induced potent inhibition of PMA-, TNF-α-, IL-1β-, and CLP-induced EPCR shedding. Lysozyme also inhibited the expression and activity of PMA-induced TACE in endothelial cells. These results demonstrate the potential of lysozyme as an anti-EPCR shedding reagent against PMA-mediated and CLP-mediated EPCR shedding.